Seven Principles of Anatomical Pedagogy in Proverbs: A Hermeneutic Study of Numerical Proverbs Based on Proverbs 6:16-19 - Aska Aprilano Pattinaja; Victor Pattianakotta (Predica Verbum: Jurnal Teologi dan Misi, 2024)
The pedagogical element is powerful in the Book of Proverbs as the primary teaching material for wisdom seekers. Interestingly, in Proverbs 6:16-19, a unique pedagogical element emerges because it is organized based on the anatomy of the human body, eyes, tongue, hands, heart, and feet. It closes with a complete picture of the human being, a false witness. Some previous studies have only focused on discussing it in terms of the structure of Proverbs 6 in the opening (prologue) of Proverbs 1-9 without examining its pedagogical elements. For this reason, this study aims to explore the pedagogical principles in Proverbs 6:16-19 as an essential lesson for a life pleasing to God and very unique because of the peculiarities of human anatomy. Based on the Hermeneutic Analysis of Wisdom Literature Sub Genre, this study found several things, namely: First, Synthetic parallelism in verse 16 emphasizes the understanding of God's hatred and disgust for sin; Second, Seven pedagogical principles of Proverbs numerical anatomy, namely: humility, honesty, mercy, purity, deliberation, honesty, and unity. The results of this study serve as a warning for believers to practice the principles of pedagogy as moral and ethical values.